Ginger (Zingiber officinale) - A Beneficial Effect on Health and Physical Activity - Popławska, Natalia Aleksandra; Śliz, Justyna; Skorupska, Marta; Czeczotka, Magdalena Joanna; Woźniak, Krzysztof (Quality in Sport, 2024)
Introduction: Ginger (Zingiber officinale) is a member of the Zingiberaceae plant family and is indigenous to Southeast Asia. It has been widely utilized as an herbal remedy in numerous nations and is known for its beneficial properties, such as anti-inflammatory, antioxidant, and anti-apoptotic effects. Ginger is commonly consumed for its various health benefits, including alleviating coughs, reducing pain, addressing nausea, aiding digestion, and exhibiting analgesic and anti-inflammatory effects. Recently, research has begun to uncover the potential benefits of ginger on physical activity and athletic performance. Materials and methods: A comprehensive examination of scientific and medical literature was performed using the PubMed and Google Scholar databases. The search terms employed were: "ginger," "ginger anticancer," "ginger anti-inflammatory," and "ginger antiemetic." Conclusion: Ginger, scientifically known as Zingiber officinale, is a widely utilized herb with various biological effects including anti-inflammatory, antioxidant, anticancer, and antibacterial properties primarily attributed to four phenolic compounds: gingerols, shogaols, paradols, and zingerone. Notably, 6-shogaol, an active ingredient in ginger, shows promise as a natural anticancer product with potential therapeutic benefits. Also, several scientific studies have indicated that ginger supplementation may lead to reduced muscle soreness, improved endurance performance, and decreased inflammation in response to intense physical activity.